Center of resistance assessment of upper lateral incisors with different dentoalveolar bone height and crown-root ratio: A finite element method study - Shivani Vaishy; Shruti S Biyani; Vinit D Swami; Vasanthi V Swami; Veera Bhosale (Wolters Kluwer Medknow Publications, 2023)
Background: In orthodontics, the type of tooth displacement is very important for determining the best way to apply force and how the teeth will move as a result. The link between a tooth's center of resistance (CRest) and the force's line of action is crucial for effective orthodontic tooth movement. To regulate tooth displacement patterns, translation, or tilting, the CRest has been a crucial point of reference. Changes in bone support brought on by dentoalveolar bone loss cause a shift in CRest. To provide the same movement in a tooth with bone loss as in a tooth with a healthy-supporting structure, modification to the applied force system is demanded. Aim: The study aimed to assess the CRest of upper lateral incisor with varying dentoalveolar bone heights and crown-root ratio, with a finite element method. Materials and Methods: Eight three-dimensional finite element models of upper lateral incisors of varying dentoalveolar bone height and root resorption were developed, and a force of 1N was applied labiolingually. The CRest is derived by altering the moment/force ratio to produce the translation by the following formula: moment = Force × distance. Results: The CRest changes more coronally as apical root resorption rises and more apically as bone loss progresses. Moment/force ratio required to produce bodily movement increases in association with dentoalveolar bone loss and decreases with root resorption. Conclusion: To maintain physiologically acceptable movements with the least amount of harm to the supporting tissues, applied force and moment magnitudes must be adjusted in response to dentoalveolar bone loss and altered crown-root ratio.